Breaking tolerance to the natural human liver autoantigen cytochrome P450 2D6 by virus infection - Holdener, Martin; Hintermann, Edith; Bayer, Monika; Rhode, Antje; Rodrigo, Evelyn; Hintereder, Gudrun; Johnson, Eric F; Gonzalez, Frank J; Pfeilschifter, Josef; Manns, Michael P; Herrath, Matthias von G; Christen, Urs (The Journal of experimental medicine, 2008)
Autoimmune liver diseases, such as autoimmune hepatitis (AIH) and primary biliary cirrhosis, often have severe consequences for the patient. Because of a lack of appropriate animal models, not much is known about their potential viral etiology. Infection by liver-tropic viruses is one possibility for the breakdown of self-tolerance. Therefore, we infected mice with adenovirus Ad5 expressing human cytochrome P450 2D6 (Ad-2D6). Ad-2D6-infected mice developed persistent autoimmune liver disease, apparent by cellular infiltration, hepatic fibrosis, "fused" liver lobules, and necrosis. Similar to type 2 AIH patients, Ad-2D6-infected mice generated type 1 liver kidney microsomal-like antibodies recognizing the immunodominant epitope WDPAQPPRD of cytochrome P450 2D6 (CYP2D6). Interestingly, Ad-2D6-infected wild-type FVB/N mice displayed exacerbated liver damage when compared with transgenic mice expressing the identical human CYP2D6 protein in the liver, indicating the presence of a stronger immunological tolerance in CYP2D6 mice. We demonstrate for the first time that infection with a virus expressing a natural human autoantigen breaks tolerance, resulting in a chronic form of severe, autoimmune liver damage. Our novel model system should be instrumental for studying mechanisms involved in the initiation, propagation, and precipitation of virus-induced autoimmune liver diseases.